Factors influencing cancer treatment decision‐making by indigenous peoples: a systematic review. Issue 2 (7th July 2015) - Tranberg, Rona; Alexander, Susan; Hatcher, Deborah; Mackey, Sandra; Shahid, Shaouli; Holden, Lynda; Kwok, Cannas
Abstract: Objective: We aim to systematically review studies that identify factors influencing cancer treatment decision‐making among indigenous peoples. Methods: Following the outline suggested by the Preferred Reporting Items for Systematic Review and Meta‐analysis, a rigorous systematic review and meta‐synthesis were conducted of factors that influence cancer treatment decision‐making by indigenous peoples. A total of 733 articles were retrieved from eight databases and a manual search. After screening the titles and abstracts, the full text of 26 articles were critically appraised, resulting in five articles that met inclusion criteria for the review. Because the five articles to be reviewed were qualitative studies, the Critical Appraisal Skills Program toolkit was used to evaluate the methodological quality. A thematic synthesis was employed to identify common themes across the studies. Results: Multiple socio‐economic and cultural factors were identified that all had the potential to influence cancer treatment decision‐making by indigenous people. These factors were distilled into four themes: spiritual beliefs, cultural influences, communication and existing healthcare systems and structures. Conclusion: Although existing research identified multiple factors influencing decision‐making, this review identified that quality studies in this domain are scarce. There is scope for further investigation, both into decision‐making factors and into the subsequent design of culturally appropriate programmes and services that meet the needs of indigenous peoples. Copyright © 2015 John Wiley & Sons, Ltd.